Effects of Virtual Reality Immersion and Audiovisual Distraction Techniques for Patients with Pruritus - Vera Leibovici; Florella Magora; Sarale Cohen; Arieh Ingber (Pain Research and Management)
BACKGROUND: Virtual reality immersion (VRI), an advanced computer-generated technique, decreased subjective reports of pain in experimental and procedural medical therapies. Furthermore, VRI significantly reduced pain-related brain activity as measured by functional magnetic resonance imaging. Resemblance between anatomical and neuroendocrine pathways of pain and pruritus may prove VRI to be a suitable adjunct for basic and clinical studies of the complex aspects of pruritus.